A methanesulfonic acid/sulfuric acid‐based route for easily‐controllable chloromethylation of poly(ether ether ketone). Issue 5 (15th September 2014) - Yan, Xiaoming; Wu, Xuemei; He, Gaohong; Gu, Shuang; Gong, Xue; Benziger, Jay
ABSTRACT A mixed methanesulfonic acid/sulfuric acid solvent based chlromethylation of poly(ether ether ketone) (PEEK) is described. Methanesulfonic acid is the solvent, sulfuric acid is the catalyst, and chloromethyl octyl ether (CMOE) is the chloromethylating reagent. 1H‐NMR spectra confirmed the successful synthesis of chloromethylated PEEK (CMPEEK). The effects of polymer concentration, catalyst/polymer ratio, and reaction temperature on the rate of PEEK chloromethylation were investigated. In order to minimize crosslinking, the PEEK concentration must be kept very low (< 2%). The reaction rate increases with increased catalyst/polymer ratio and reaction temperature. The activation energy of PEEK chloromethylation is 30.9 kJ mol−1. The extent of reaction for the new route is more easily controllable as compared with the previous sulfuric acid based route. The reaction rate constant at 25°C for the new route is 1.29 h−1 which is lower than that for chloromethylation by concentrated sulfuric acid at −10°C (rate constant 1.88 h−1). As a result, the degree of chloromethylation of CMPEEK can be easily controlled at room temperature using this mixed solvent. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41404.